The Effects of 24-Hour Sleep Deprivation on Cognitive and Motor Skills of Male College Students - Iman Ghanbari; Hamid Reza Taheri; Mahdi Sohrabi (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Sleep is assumed to be a critical factor for human physiological and cognitive function. Lack of sleep is a common condition in daily life. Objectives. The purpose of this study was to evaluate the effects of 24-hour sleep deprivation on cognitive and motor skills in university students. Methods. The participants were volunteers that consisted of 290 male students aged 19-25 years. After primary screening, the subjects were randomly divided into two groups of cognitive tests and motor task test. Cognitive tests were included the reaction time (simple and choice), the working memory test (1-back & 2-back task) and attention (selective and divided). In the motor group, the subjects were divided into four experimental groups including (physical, observational, mental and combined training) and four paired control groups who were exposed to badminton short service training. The experimental groups were trained with 24-h sleep deprivation and the control group was trained without sleep deprivation. In the acquisition stage, each subject was trained using his routine training method. After training, the subjects were followed a normal day-night sleep pattern. At 24, 72 and 168 h after acquisition, a short-service retention test was taken from participants. Results. The results of cognitive tests showed that sleep deprivation had no effect on reaction time, working memory (1-back) and selective attention, but it had a major effect on working memory (2-back) and divided attention (p=0.02). The results of motor test showed that sleep deprivation did not have an effect on acquisition and retention in both physical and combined groups. (p>0.05).Sleep deprivation did not have an effect on the skill acquisition in the observation group (p>0.05); however, in the retention tests, the control group significantly showed a better performance. Skill acquisition in the mental training group was significantly affected by sleep deprivation and this effect was obvious in the retention tests (p=0.0001). Conclusion. The results showed that, under conditions of sleep deprivation, some cognitive functions (working memory 2-back test & divided attention) were affected and that physical and combined training were preferred at the time of training to acquire new motor skills.